2020
DOI: 10.1186/s12935-020-01182-2
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA NEAT1/miR-338-3p axis impedes the progression of acute myeloid leukemia via regulating CREBRF

Abstract: Background: Acute myeloid leukemia (AML) is a heterogeneous hematological disease. Our purpose of the research was to investigate the regulatory influence of long non-coding RNA (lncRNA) nuclear enriched abundant transcript 1 (NEAT1)/microRNA-338-3p (miR-338-3p)/CREB3 regulatory factor (CREBRF) in AML progression. Methods: The associated RNA and protein levels were measured by quantitative real-time polymerase chain reaction (qRT-PCR) and Western blot, respectively. Cell growth was assessed through colony form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 42 publications
(39 reference statements)
0
24
0
Order By: Relevance
“…In another study, lncRNA NEAT1 was shown to facilitate the progression of gallbladder cancer via the upregulation of Survivin expression, suggesting its potential use as a biomarker in gallbladder cancer 34 . Multiple other studies show NEAT1 associations with osteoarthritis 35 , lung cancer 36 , and acute myeloid leukemia 37 . USP3-AS1 has also been reported as a potential biomarker for neuroblastoma pathogenesis studies 38 .…”
Section: Discussionmentioning
confidence: 92%
“…In another study, lncRNA NEAT1 was shown to facilitate the progression of gallbladder cancer via the upregulation of Survivin expression, suggesting its potential use as a biomarker in gallbladder cancer 34 . Multiple other studies show NEAT1 associations with osteoarthritis 35 , lung cancer 36 , and acute myeloid leukemia 37 . USP3-AS1 has also been reported as a potential biomarker for neuroblastoma pathogenesis studies 38 .…”
Section: Discussionmentioning
confidence: 92%
“…CREB3 functions as a tumor suppressor of glioblastoma via inhibition of hypoxia-induced autophagy [73]. NEAT1 upregulated CREBRF via miR-338-3p sponging to suppress AML cell growth and migration, while induction of apoptosis [74]. CRNDE is an oncogenic lncRNA involved in tumor cell proliferation and migration [75].…”
Section: Long Non-coding Rnamentioning
confidence: 99%
“…So far, a variety of cytogenetic and molecular indicators have been widely recognized in clinical practice and become a powerful tool to assist diagnosis, guide treatment, and prognosis stratification. In recent years, a large number of researches focusing on DNA mutation, microRNA, and lncRNA are widely carried out, aiming to find more biological indicators of AML and improve the understanding of the characteristics of leukemia, so as to help monitor minimal residual lesions, improve the ability of early warning, and develop new targeted therapeutic drugs [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%